(3GdEYdGe GdCefj (B/s - (3NVhQ, COjHs ((3OeTb (B:s (3COjH NVhQ ,s, 2002)
(3jMGhd GdcJGH eYGdLI gPg GdeSGFd h jbOe GLhHI YdejI Yf gPg GdeSCdI JSge aj JhVjM eaghe LOjO dEYdGe Cefj YQHj YUQj h eJWhQ GdCeQ GdPj jOaY eSJhi GdCOGA GdEYdGej GdCefj GdYQHj h GdEYdGe GdYQHj YeheG hgh GdgOa GdeQcRj aj gPg GdSdSdIs
(3HHdjhZQGajG (B: (3U(B.131-134s
Keywords: (3GdEYdGe GdCefjs; (3GdEYdGes